The influence of overprotective parenting patterns on adolescent identity formation and social adaptation: A family communication and relationship perspective - Sihombing, Sulaiman; Utami Daulay, Aisyah Futri (The Journal of Religion and Communication Studies, 2025)
Background: Many people say that adolescence is a beautiful period because during this period, a person can have more social interactions with friends, begin to feel attracted to other types and is a time to find one's identity. It has broad implications for teenagers' lives outside the family in their relationships with peers, teachers and other adults. The emotional atmosphere of the family, the way parents train and teach their children can shape the future direction of a teenager's life. Methods: This research uses a qualitative approach with library research methods. The data that has been collected is analyzed using the content analysis method, which aims to understand and interpret the meaning contained in the texts read. Findings: This article highlights the influence of parents' overprotective behavior on adolescents' adjustment to their identity. It is important for parents to strike a balance between providing support and allowing adolescents to face their own challenges. Providing space for teenagers to make decisions, learn from mistakes, and develop independence will help them in the process of adjustment and forming a healthy identity. This balanced approach will encourage teenagers to become individuals who are more confident, independent and able to adapt to their social environment. Conclusion: Parents' overprotective behavior can cause children's bad behavior towards their parents. And parents must know that teenagers need to adapt to the environment, the people around them, teenagers are rebels and if they are forbidden, they will act more aggressively because adolescence is a time of rebellion, unstable emotions, so adjusting to the people around them or their friends is difficult. Novelty/Originality of This Study: This study explores the specific impact of overprotective parenting on adolescent identity formation and social adaptation, highlighting the need for a balance between parental control and independence.